Incidence, Causes, and Perinatal Outcomes of “Near-Miss” Obstetric Emergencies during the COVID-19 Pandemic: Experience from a Tertiary Referral Center of Western Rajasthan, India - Garima Yadav; Charu Sharma; Pratibha Singh; Vrushti Solanki; Swati Chhabra; Priyanka Kathuria; Meenakshi Gothwal; Manisha Jhirwal; Shashank Shekhar (Indian Journal of Community Medicine)
Background: Pregnant women and neonates are often considered as being a vulnerable group during the coronavirus disease 2019 (COVID-19) pandemic. Several studies have compared the impact of COVID-19 on pregnant and nonpregnant women. This study aimed to examine the reasons for severe acute maternal morbidity (SAMM) and “near-miss cases” and their effects on perinatal outcomes before and during the COVID-19 pandemic. Materials and Methods: All women admitted to our facility with pregnancy-related complications for birth or in the puerperium who required critical care unit (CCU) or high dependency unit (HDU) admission were included in the study. A modified version of the World Health Organization (WHO)’s Maternal Near-Miss Screening Tool was used to identify maternal near-miss cases and other obstetric emergencies requiring CCU admission. Results: The incidence of “near-miss” obstetric emergencies was -30.7 per 1000 live births. Over the 3 years of data obtained, 152 near-miss cases were found. Thirty-five cases were seen in the pre-COVID-19 period, whereas 117 near-miss cases were noted during the COVID-19 pandemic. The most common cause of near-miss cases in both groups was severe preeclampsia (65.8%). The rate of ICU admissions was 80.3% (94/117) during COVID-19, while only three cases required ICU before the COVID-19 pandemic. There were a total of 11 maternal deaths, and all were reported during the COVID-19 pandemic. Conclusion: There was a significant increase in ICU admission rates and “near-miss” obstetric emergencies during the COVID-19 pandemic. The COVID-19 infection indirectly led to higher maternal morbidity secondary to lockdown effects on antenatal care and delayed referrals. This study will contribute to the existing literature on the impact of the COVID-19 pandemic on maternal and child health. The results will help inform policy decisions and guide the development of interventions to improve the quality of care for pregnant women during the pandemic.